C6–H Bond Functionalization of Indoles: A New Gate - Taskesenligil, Yunus; Saracoglu, Nurullah (Synthesis, 2023)
Indoles are valuable precursors in medicinal, bioorganic, and material chemistry and particularly serve as a platform for diversity. However, the scope of the C6-functionalization of indoles was limited until recently. In this short review, we summarize developments in the C6-functionalization reactions of indoles involving transition-metal-catalyzed functionalization and Brønsted and Lewis acid catalyzed processes. The regioselectivity is controlled by remote-C–H activation and hydrogen bond formation.1 Introduction2 Transition-Metal-Catalyzed Functionalization3 Acid-Catalyzed Processes4 Conclusion
Keywords: indole; C–H bond activation; directing group (DG); transition metal (TM); acid catalyst; hydrogen bond; electrophilic aromatic substitution (EAS)